Determination of the levels of 17-?Estradiol and Progesterone in Cow milk and Baby Follow-on milk by ELISA - Seker, Pinar; Risvanli, Ali; Seker, Ibrahim; Calicioglu, Mehmet (Univ Zulia, Facultad Ciencias Veterinarias, 2023)
The current study was undertaken to determine the 17-13 Estradiol (E2) and Progesterone (P4) levels in different milk products and some baby follow-on milk samples collected from retail markets in Turkiye. For this purpose, a total of 50 samples from 8 different product groups with different fat levels, production technologies, and production series were analyzed for natural P4 and E2 levels using a commercial ELISA kit. The highest E2 level was determined in UHT whole milk (3%) (39.20 +/- 6.73 pmol center dot L-1) while the lowest level was found in buttermilk (26.50 +/- 1.85 pmol center dot L-1) samples. For P4 levels, the highest concentration were found in baby follow-on milk (<1 year old) (45.83 +/- 2.95 nmol center dot L-1) and the lowest values were found in pasteurized milk samples (23.00 +/- 6.66 nmol center dot L-1). Also, in this study, differences among the product groups for E2 and P4 were not found statistically (P>0.05). In conclusion, the natural P4 and E2 were detected in all milk and baby follow-on milks at various levels and generally their levels associated with the product fat level.
Determinación de los niveles de 17-? estradiol y progesterona en leche de vaca y leche de continuación para bebés mediante ELISA
Keywords: Progesterone; estradiol 17-13; milk; babyfollow-on milk; ELISA